Successful thrombo-embolectomy in long-standing thrombo-embolic pulmonary hypertension. Issue 2 (March 1968) - Nash, E. S.; Shapiro, S.; Landau, A.; Barnard, C. N.
Abstract : The operative removal of thrombo-emboli from the pulmonary arteries in acute pulmonary embolism is an accepted method of treatment. The removal of thrombi that have been present for many months has been attempted less often. This case report covers the operative treatment and the pre- and post-operative physiological studies in a patient with long-standing thrombo-embolic pulmonary hypertension, in whom a large thrombus was removed under cardiopulmonary bypass from the left pulmonary artery. Dramatic clinical improvement resulted. A plea is made for a more radical approach to thrombo-embolic pulmonary hypertension when a local obstruction can be demonstrated.